Colchicine as adjuvant therapy in COVID-19 patients: A meta-analysis - Betty Rachma; Probo Yudha Pratama Putra; Zakiya Zulaifah; Arlinda Silva Prameswari; Dinda Amalia Eka Putri (International Journal of Public Health Science (IJPHS), 2022)
SARS CoV-2 infection results in hyperinflammatory responses through the activation of proinflammatory cytokines and chemokines. Colchicine is an anti-inflammatory drug that reduces superoxide production, TNF-a activation, and neutrophil chemotaxis. This study aims to determine the effect of adjuvant colchicine on mortality in COVID-19 patients. Systematic literature searching was conducted on PubMed, ScienceDirect, Cochrane Library, and medRxiv with keywords colchicine, Coronavirus Disease, COVID-19, SARS CoV-2, and mortality. Five randomized controlled studies with 15.779 patients were included. There was no significant difference between colchicine group and standard group (OR 1.00 [95% CI 0.91-1.09], p=0.94), Invasive mechanical ventilation necessity also did not show significant difference (OR 0.99 [95% CI 0.83-1.17 p=0.88). There was no significant difference in the incidence of cardiovascular disease (OR 1.11 [95% CI 0.50-2.46], p = 0.79), also the incidence of pneumonia was lower in colchicine group (OR 0.68 [95% CI 0.49-0.93], p=0.02), while the incidence of gastrointestinal complaints was higher in colchicine group (OR 2.09 [95% CI 1.84-2.37], p<0.00001). Colchicine as COVID-19 adjuvant therapy did not significantly reduce mortality, the need for invasive mechanical ventilation, and the incidence of cardiovascular disease. Furthermore, the colchicine group had lower pneumonia incidence and higher gastrointestinal complaints incidence.